Factores de riesgo asociados a mortalidad en pacientes con Covid-19 hospitalizados en la unidad de cuidados intensivos del Hospital Regional de Loreto 2021 - Zumaeta Córdova, Chaner (2024)
COVID-19 generated a very high mortality, mainly in the ICU due to little knowledge of the disease and its treatment. The main objective was to identify the Risk Factors associated with mortality in patients treated in the ICU of the Loreto Regional Hospital from January to July 2021, through a retrospective Case-Control study. 200 patients were studied. Of these, 113 patients died (56.50%) and 87 (43.50%) survived, 127 (63.50%) were men and the average age was 55.22 ± 13.04 years (mean ± standard deviation). In those who died; The mean age was 58.08 ± 13.8, 48.7% had hypertension, 83.19% had PaFio2 ≤ 200, 77.9% required vasopressors, and 33.6% underwent hemodialysis. In the bivariate regression analysis, it was found: age (OR 1.04; 95% CI: 1.01 1.06; p = 0.001), arterial hypertension (OR 2.10; 95% CI: 1.17-3.78; p = 0.013), PaO2/FiO2 of 200 or less (OR 2.22; 95% CI: 1.13-4.35; p = 0.019), use of vasoactive agents (OR 5.75; 95% CI: 3.09-10.71; p < 0.001), hemodialysis (OR 5.00; 95% CI 2.19-11.42; p < 0.001). In the multivariate regression analysis, the only association that was lost was that of arterial hypertension (OR: 1.52; 95% CI: 0.73-3.16; p = 0.253). It is concluded: a high prevalence of younger patients compared to the rest of the world. Furthermore, the use of vasoactive agents, having had at least one hemodialysis session, a PaO2/FiO2 ≤ 200 and a stay in the ICU of less than 12 days increased the risk of mortality.